Pelatihan Aplikasi Edmodo Untuk Meningkatkan Motivasi Belajar Daring Pada Masa Pandemi Covid-19 Di Exact Media Center Kota Padangsidimpuan - Yusra Fadhillah; Muhammad Noor Hasan Siregar; Novita Aswan (Yayasan Kajian Riset dan Pengembangan RADISI, 2021)
The global spread of COVID-19 has an impact on all aspects of life, including the education aspect. Under these circumstances, an effective learning strategy is needed to achieve the learning objectives. Learning is the main thing in an educational institution, so a good learning process will produce good graduates as well. This situation certainly needs to be improved by improving learning facilities to improve the online learning process. The lack of knowledge of using e-learning makes it difficult for tutors and students to carry out online learning. Therefore, through this community service program, it is hoped that it can support and improve the learning process, especially the use of e-learning learning media. The purpose of this service activity is carried out in the form of training starting from the introduction of the Edmodo application for the learning management system, then how to use the application with various features to make it easier for tutors and students in delivering material. The method of implementing this service is carried out through several stages, namely, socialization, training, practice and monitoring. The target of this activity is EMC tutors and students in Padangsidimpuan City. The results of the evaluation of the implementation of this training show that this activity is useful to support the teaching and learning process carried out at the EMC tutoring place. This training is able to improve the skills of tutors and students in using Edmodo e-learning media, and the conclusion in this activity is the knowledge of using Edmodo e-learning media for tutors and students, so it is hoped that in the future the EMC tutors can use e-learning media as supporting learning activities